2021
DOI: 10.3390/jcm10091904
|View full text |Cite
|
Sign up to set email alerts
|

Facial Affect Recognition by Patients with Schizophrenia Using Human Avatars

Abstract: People with schizophrenia have difficulty recognizing the emotions in the facial expressions of others, which affects their social interaction and functioning in the community. Static stimuli such as photographs have been used traditionally to examine deficiencies in the recognition of emotions in patients with schizophrenia, which has been criticized by some authors for lacking the dynamism that real facial stimuli have. With the aim of overcoming these drawbacks, in recent years, the creation and validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(81 reference statements)
2
8
0
Order By: Relevance
“…Virtual reality may turn out to be the future direction of the development of programs aimed at training the recognition of the expression of Archives of Psychiatry and Psychotherapy, 2023; 1: 24-32 facial emotions. The results confirm that deficits in recognizing emotions also occur when reading them from the dynamic faces of avatars [71]. Virtual reality allows you to create situations in which the subject will have to recognize emotions in everyday life.…”
Section: Therapeutic Interactionssupporting
confidence: 69%
“…Virtual reality may turn out to be the future direction of the development of programs aimed at training the recognition of the expression of Archives of Psychiatry and Psychotherapy, 2023; 1: 24-32 facial emotions. The results confirm that deficits in recognizing emotions also occur when reading them from the dynamic faces of avatars [71]. Virtual reality allows you to create situations in which the subject will have to recognize emotions in everyday life.…”
Section: Therapeutic Interactionssupporting
confidence: 69%
“…Findings from empirical studies have shown that PLwS present more severe impairments in recognizing negative and neutral emotions, such as anger, fear, and calmness, while they do not present difficulties in recognizing positive emotions, such as happiness ( 1 , 57 , 58 ). Similarly, the meta-analysis found the greatest levels of impairments in identifying fear, disgust, anger, and sadness emotions in Chinese PLwS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of avatars in treating illnesses has advanced in recent years, offering many possibilities in terms of the pathologies they are geared towards. Although not all the benefits of this kind of intervention are currently known, good results have been obtained in the treatment of anxiety in disorders such as agoraphobia [20] and social phobia [17][18][19], as well as in treating eating disorders [13,14], addictions [15,16], weight control [9][10][11], facial pattern recognition [26][27][28][29][30], and ASD [31][32][33]. Education is another area in which they have been used.…”
Section: Discussionmentioning
confidence: 99%
“…The results found in the scientific literature suggest that immersive virtual reality, through the use of avatars, can be used as a tool for training patients in recognizing emotions [26]. This finding is particularly useful for people with schizophrenia, as they find it difficult to recognize facial emotions, causing alterations in their interpersonal relationships [27,28]. Its usefulness has also been established for people with autism, given their deficiency in social cognition and communication [29], and for major depressive disorders in which patients have a negative response bias towards sadness, tending to assess positive, neutral, and ambiguous facial expressions as being sadder [30].…”
Section: Introductionmentioning
confidence: 99%